Effects of Apolipoprotein E Polymorphism on Cerebral Oxygen Saturation After Traumatic Brain Injury - Wu, Zhimin; Xiong, Senjie; Sun, Xiaochuan; Shi, Quanhong; Dan, Wei; Zhan, Yan; Xie, Yanfeng; Jiang, Li (Frontiers in Neurology, 2020)
Objective: To investigate the effect of the apolipoprotein E gene (APOE) on cerebral oxygen saturation of patients after traumatic brain injury (TBI). Methods: Clinical data of 114 patients with TBI and 54 normal people were collected, and the APOE genotypes of all subjects were determined by multiple quantitative fluorescent polymerase chain reaction (QF-PCR). The regional cerebral oxygen saturation (rScO2) of TBI patients and normal people were monitored by Near-infrared spectroscopy (NIRS). Results: The mean rScO2 of patients was (55.06±7.60)% in the early stage of TBI, which was significantly lower than that of normal people (67.21±7.80)% (P <0.05). Single-factor and multi-factor logic analysis showed APOEε4 was independent risk factors that caused the early decline of rScO2 in TBI patients. Furthermore, in the TBI group, the rScO2 of APOEε4 carriers (52.23±8.02)% was significantly lower than that of non-ε4 carriers (60.33±7.12)% (P<0.05). But in the normal group, no significant differences of rScO2 were found between APOEε4 carriers and non-carriers. Conclusion: The rScO2 of patients was significantly decreased after TBI, and APOEε4 may be a risk factor for decreased brain oxygen saturation in the early stage of TBI.